Hands-on Solar Energy: Exploring How Light Influence Solar Cell Performance in Junior High School Experiments - Wahidin, Naufal Rabah; Prima, Eka Cahya; Riandi, Riandi (Universitas Nurul Huda, 2024)
This study explores the impact of light wavelength on solar cell performance through a hands-on laboratory experiment designed for junior high school students. The experiment utilized a spectrometer app to measure the dominant wavelengths of various visible light colors and assessed the corresponding voltage and current generated by a solar cell. Results indicated a clear inverse relationship between wavelength and solar cell output, with shorter wavelengths producing higher voltage and current values. For example, light with a wavelength of 400 nm resulted in the highest voltage (1.75 V) and current (13.9 µA), whereas light at 650 nm generated the lowest output (1.43 V and 8.7 µA). This experiment provides an accessible, cost-effective way for students to grasp the principles of solar energy and wavelength effects, enhancing their understanding of energy conversion in renewable technologies.